2009
DOI: 10.1002/cbf.1559
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of diphenyl diselenide on oxidative stress caused by acute physical exercise in skeletal muscle and lungs of mice

Abstract: This study was designed to examine if diphenyl diselenide (PhSe) 2 , an organoselenium compound, attenuates oxidative stress caused by acute physical exercise in skeletal muscle and lungs of mice. Swiss mice were pre-treated with (PhSe) 2 (5 mg kg -1 day -1 ) for 7 days. At the 7th day, the animals were submitted to acute physical exercise which consisted of continuous swimming for 20 min. The animals were euthanized 1 and 24 h after the exercise test. The levels of thiobarbituric acid reactive species (TBARS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Regarding laboratory animals, several studies have reported exercise-induced alterations in redox homeostasis in Wistar rats (Veskoukis et al, 2008), Sprague-Dawley rats (Gul et al, 2006;Nie et al, 2010) and Fischer 344 rats (Bejma et al, 2000). Similarly, alterations in redox homeostasis have been reported in mdx mice [an animal model for Duchenne muscular dystrophy, which lacks dystrophin (Radley-Crabb et al, 2011)], C57/BL6J mice (Yokota et al, 2009), BALB/c mice (De la Fuente et al, 1995), Swiss mice (Prigol et al, 2009), Hsd:ICR mice, which had been selected for high wheel-running activity (Vaanholt et al, 2008), and guinea pigs (De la Fuente et al, 1995). Finally, exercise has been reported to induce alterations in redox homeostasis in fish (Aniagu et al, 2006), birds (Costantini et al, 2008;Costantini and Lipp, 2010;Larcombe et al, 2010), dogs (Wyse et al, 2005) and horses (Kinnunen et al, 2009).…”
Section: Acute Exercise Alters Redox Homeostasis Across Strains and Smentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding laboratory animals, several studies have reported exercise-induced alterations in redox homeostasis in Wistar rats (Veskoukis et al, 2008), Sprague-Dawley rats (Gul et al, 2006;Nie et al, 2010) and Fischer 344 rats (Bejma et al, 2000). Similarly, alterations in redox homeostasis have been reported in mdx mice [an animal model for Duchenne muscular dystrophy, which lacks dystrophin (Radley-Crabb et al, 2011)], C57/BL6J mice (Yokota et al, 2009), BALB/c mice (De la Fuente et al, 1995), Swiss mice (Prigol et al, 2009), Hsd:ICR mice, which had been selected for high wheel-running activity (Vaanholt et al, 2008), and guinea pigs (De la Fuente et al, 1995). Finally, exercise has been reported to induce alterations in redox homeostasis in fish (Aniagu et al, 2006), birds (Costantini et al, 2008;Costantini and Lipp, 2010;Larcombe et al, 2010), dogs (Wyse et al, 2005) and horses (Kinnunen et al, 2009).…”
Section: Acute Exercise Alters Redox Homeostasis Across Strains and Smentioning
confidence: 97%
“…Based on studies that have measured redox homeostasis in tissues other than blood and skeletal muscle, it is certain that acute exercise alters redox homeostasis in practically every fluid, blood cell, tissue and organ. In fact, several studies have found alterations in redox homeostasis after acute exercise in exhaled breath (Mercken et al, 2005), urine (McAnulty et al, 2010), lymphocytes (Boudreau et al, 2005), neutrophils (Sureda et al, 2005), diaphragm (Itoh et al, 2004), heart (Nie et al, 2010), liver (Liu et al, 2000), lung (Prigol et al, 2009), spleen (Kruger et al, 2009), thymus , kidney (Leeuwenburgh and Ji, 1995) and brain (Lappalainen et al, 2010). This is not to imply that all tissues respond both qualitatively and quantitatively in a similar way to the same exercise stimulus.…”
Section: Effects Of Very Short Duration Exercise On Redox Homeostasismentioning
confidence: 99%
“…21 The research more and more often includes selenoorganic compounds -either naturally occurring forms or newly synthesized substances, e.g., selenomethionine, naphthalimide-based selenocyanates, 2-(5-selenocyanatopentyl)-benzo[de]isoquinoline-1,3-dione, diphenyl diselenide, selenofuranoside, p-methoxyldiphenyl diselenide, selenocyanates, and diphenylmethyl selenocyanate. [4][5][6]9,16,17,19,20,[22][23][24][25][26] The results regarding the comparison of inorganic and organic compounds are not fully consistent, although the newest studies usually reveal plasma urea and plasma creatinine ↑; kidney vitamin C, GSH, GST, GPx, GR, CAT, δ-ALA-D ↓ p-methoxyl-diphenyl diselenide 50 mg/kg or 100 mg/kg, orally 6 days lower dose: plasma urea (±); plasma creatinine (0); kidney GSH, GST, GPx, GR, δ-ALA-D (±); kidney vitamin C, CAT (+) higher dose: plasma urea and plasma creatinine (±), kidney GSH, GST, GPx, GR, vitamin C, CAT (+) kidney δ-ALA-D (±) none ↓ -decrease; ↑ -increase; (+) -full protection; (±) -partial protection; (0) -lack of protection; GST -glutathione S-transferase; GPx -glutathione peroxidase; CAT -catalase; SOD -superoxide dismutase; GSH -reduced glutathione; TBARS -thiobarbituric acid-reactive substances; GR -glutathione reductase; δ-ALA-D -δ-aminolevulinic dehydratase..…”
Section: Comparison Of the Effect Of Different Selenium Forms On Orgamentioning
confidence: 99%
“…11,13 As the interest in selenium and its effects on human health is still growing, diverse compounds of selenium are still being studied, both inorganic and organic, Se-enriched natural products like probiotics, yeast and green tea, as well as selenium nanoparticles. 3,8,10,[14][15][16][17][18] Organic compounds have been widely studied recently due to the similarity of the activity of some of them (e.g., ebselen or diphenyl diselenide) to that shown by glutathione peroxidase. 19 Diphenyl diselenide has also been proved to possess many beneficial pharmacological properties: anti-hyperglycemic, anti-hyperlipidemic, hepatoprotective, antiulcer, and antidepressant.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, the interest in organoselenium biochemistry and pharmacology has increased due to a variety of compounds that show biological activity (May, 1999;Nogueira et al, 2004, Nogueira & Rocha, 2011. In fact, its compounds show antioxidant (Gerzson et al, 2012;Luchese et al, 2009;Nogueira et al, 2004;Prigol et al, 2009), neuroprotective (Porciúncula et al, 2003), antidepressant-like (Gerzson et al, 2012;Oliveira et al, 2012;Savegnago et al, 2008), antihypertensive, anticancer, antiviral, immunosuppressive, and antimicrobial properties (May, 1999;Nogueira et al, 2004;Schewe, 1995). Recently, our group of research showed hepatoprotective effect of bis(4-methylbenzoyl) diselenide (BMD), an disubstituted diaryl diselenide, against carbon tetrachloride (CCl 4 )-induced oxidative damage in mice possibly by modulating the antioxidant status (Filho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%